압연 온도와 압연량이 다른 STS202의 탄성파 특성 - 남기우(Ki-Woo Nam); 전현(Hyun Jeon); 이기식(Ki-Sik Lee); 탁영준(Young-Joon Tak) (동력시스템공학회지, 2021)
이 논문에서는 202 오스테나이트계 스테인리스강의 생산 단가 저감을 위하여 고가인 Cr과 Ni 성분을 줄이고, 저가인 Mn을 첨가하였다. 202 오스테나이트 스테인리스강은 압연 온도와 압연량을 달리하여, 마르텐사이트 양을 다르게 생성하였다. 압연 온도 및 압연량이 다른 인장시험편에서 발생하는 탄성파를 검출하여, 시간-주파수 해석법으로 탁월주파수를 조사하였다. In this study, high-cost Cr and Ni components of 202 austenitic stainless steel were reduced, low-cost Mn was added, and the amount of martensite and mechanical properties were evaluated according to rolling temperature and rolling degree. In addition, the acoustic wave generated by internal deformation during tension test was detected, and the dominant frequency according to the amount of martensite was investigated by wavelet analysis. Parts of the austenite were transformed into ′ -martensite by rolling. More martensite was generated as the rolling degree was increased, and more martensite was generated as the rolling temperature decreased in the same rolling degree. The amount of martensite rapidly increased up to a rolling degree of 33%, and then gradually increased thereafter. In particular, the amount of martensite at rolling temperature of -196℃ was similar after the rolling degree of 33%. Vickers hardness and tensile (yield) strength increased as the rolling temperature decreased and the rolling degree increased. The elongation decreased rapidly. The dominant frequency decreased after increasing as the rolling degree increased at each rolling temperature, and the highest value was shown at 33% of the rolling degree. KCI Citation Count: 2